0784 Defining Disrupted Nighttime Sleep in Pediatric Narcolepsy. (27th April 2018) - Maski, K P; Little, E; Steinhart, E; Colclasure, A; Scammell, T; Diniz Behn, C
Abstract: Introduction: Disrupted nighttime sleep (DNS) is a core narcolepsy symptom and likely reflects the sleep/wake state instability that emerges with hypocretin neuronal loss. Objective DNS definitions vary and include increases in NREM stage 1 (N1) sleep, decreased sleep efficiency (SE), increased wake bout number and increased wake and N1 transitions out of sleep. Narcolepsy typically starts before age 20 years, but it is unknown how DNS presents in pediatric patients. We determined objective measures of DNS in pediatric narcolepsy and explored their association with mean sleep latency scores (MSL) on the multiple sleep latency test (MSLT). Methods: We studied nocturnal polysomnograms of 14 subjects ages 6–18 years of age with narcolepsy type 1 and 14 age- and gender-matched controls. Subjects were drug-naïve at testing, and controls represent patients with subjective sleepiness but normal MSLT results. We compared sleep measures using t-tests, and we analyzed maintenance of wake, NREM (combined N2 and N3) and REM sleep using log-rank tests to compare Kaplan-Meier survival curves of bout durations. We also assessed correlations between sleep measures and MSL values. Results: The narcolepsy group had more sleep transitions to states of wake and N1 than controls (P=0.01), but we found no differences in N1 sleep percentage, SE, or wake bout number (P>0.05). In contrast to controls, narcolepsy patients were unable to sustain long wake bouts (P<0.001). The increase in sleep transitions resulted in less NREM sleep consolidation in the narcolepsy group compared to controls (P<0.003); a similar trend was noted for REM sleep (P=0.06). Furthermore, the number of sleep transitions to wake or N1 correlated with MSL values across subjects (r=-0.5, P=0.01) whereas other sleep measures did not (P>0.05). Conclusion: In pediatric narcolepsy, DNS is characterized by frequent transitions from sleep to N1 sleep and brief wake periods that result in short NREM sleep bouts. Importantly, the severity of this DNS measure predicts MSL values, suggesting that DNS contributes to daytime sleepiness and thus may benefit from treatment. Support (If Any): Investigator initiated grant to Dr. Kiran Maski from Jazz Pharmaceuticals, Inc.